A revisit to the practice of late payment charges by Islamic Banks in Malaysia - Ezani Yaakub,; Mohamed Azam Mohamed Adil,; Asmak Husin,; Mohd Dani Muhamad,; Mohammad Mahyuddin Khalid,; Mohd Solahuddin Shahruddin, (Penerbit Universiti Kebangsaan Malaysia, 2014)
Islamic banking in Malaysia have been experiencing late payment and default issues because customers are not allowed to be charged with interest (riba) as opposed to the practices in the conventional banking. To mitigate these issues, the Shariah Advisory Council of Bank Negara Malaysia has enforced ta’widh and gharamah as regulatory alternatives. Practically, ta’widh and gharamah were imposed on the defaulting customers who fail to meet their obligation to pay their financing based on several conditions. Given the significance of its imposition, this paper aims to analyse the current practice in Islamic banks and examine the views of contemporary Muslim scholars on ta’widh and gharamah and its suitability as alternatives for avoidance of riba.